(13b-2)-3(4b+4)=-3
(13b-2)+(-3(4b+4))=-3
(13b-2)+(-12b-12)=-3
13b-2-12b-12=-3
13b-12b-2-12=-3
1b-14=-3
b=11
(13*11)-3(4*11+4)=
141-3(48)=
141-144=-3
2006-11-15 14:37:44
·
answer #1
·
answered by Richard 7
·
0⤊
0⤋
(13b - 2) - 3(4b + 4) = -3 ... Distribute the 3 ...
13b - 2 - 12b - 12 = -3 ... Combine like terms ...
b - 14 = -3 ... Add 14 to both sides ...
b = 11
2006-11-15 22:30:46
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
13b-2-12b-12=-3 b-14=-3 b=-3+14 b=11
2006-11-15 22:33:07
·
answer #3
·
answered by sam 3
·
0⤊
0⤋
(13b - 2) - 3(4b + 4) = -3
(13b - 2) - 12b - 12 = -3
b - 14 = -3
b = 11
2006-11-15 22:31:00
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
(13b-2) - 3(4b+4) = -3
13b - 2 - 12b - 12 = -3
13b - 12 b = -3 + 2 + 12
b = 11
2006-11-15 22:30:34
·
answer #5
·
answered by darkskaners 3
·
0⤊
0⤋
(13b -2) - 3(4b+4) = -3
13b - 2 - 12b - 12 = -3
1b - 14 = -3
1b = 11
b = 11
2006-11-15 22:32:23
·
answer #6
·
answered by A.J. 1
·
0⤊
0⤋
first ,expand this formula ,then you will get
13b-2-12b-12=-3
b-14=-3 so b=11
2006-11-15 22:31:47
·
answer #7
·
answered by peterwan1982 2
·
0⤊
0⤋
13b-2-12b-12=-3
b-14=-3
adding 14
b=11
2006-11-15 22:31:07
·
answer #8
·
answered by raj 7
·
0⤊
0⤋
13b-2-12b-12=-3
b-14=-3
b=-3+14
b=11
2006-11-15 22:29:55
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
(13b-2)-12b-12=-3
b-14=-3
b=11
2006-11-15 22:31:09
·
answer #10
·
answered by loverbear20022002 2
·
0⤊
0⤋